Jawapan

2016-03-07T12:45:18+08:00
F(x) = 2x - 1

f(x) = 9
2x - 1 = 9
2x = 10
x = 10/2
x = 5
2016-03-07T12:49:42+08:00
9 = 2x - 1                                                                                                         9 + 1 = 2x                                                                                                       10 = 2x                                                                                                           10/2 = x                                                                                                         5 = x